Comparison of Van Allen Probes radiation belt proton data with test particle simulation for the 17 March 2015 storm. Issue 11 (22nd November 2016) - Engel, M. A.; Kress, B. T.; Hudson, M. K.; Selesnick, R. S.
Abstract: The loss of protons in the outer part of the inner radiation belt ( L = 2 to 3) during the 17 March 2015 geomagnetic storm was investigated using test particle simulations that follow full Lorentz trajectories with both magnetic and electric fields calculated from an empirical model. The simulation results presented here are compared with proton pitch angle measurements from the Van Allen Probe satellites Relativistic Electron Proton Telescope (REPT) instrument before and after the coronal mass ejection‐shock‐driven storm of 17–18 March 2015, with minimum Dst =− 223 nT, the strongest storm of Solar Cycle 24, for four different energy ranges with 30, 38, 50, and 66 MeV mean energies. Two simulations have been run, one with an inductive electric field and one without. All four energy channels show good agreement with the Van Allen Probes REPT measurements for low L ( L < 2.4) in both simulations but diverge for higher L values. The inclusion of the inductive electric field, calculated from the time‐changing magnetic field, significantly improves the agreement between simulation and REPT measurements at L > 2.4. A previous study using the Highly Elliptical Orbiter 3 spacecraft also showed improved agreement when including the inductive electric field but was unable to compare effects on the pitch angle distributions. Key Points: Including an inductive electric field from time‐stepping TS05 improves accuracy of simulation Comparison of simulation with Van Allen Probes data shows good agreement with changes in pitch angle distribution The field line curvature scattering that dominates the loss mechanisms in the simulations is pitch angle dependent